The complete book of running - Fixx, James F. (New York : Random House, 1977)
Provides information on many facets of running, including physical and psychological benefits, techniques, clothing, races, and other subjects.
Includes index.
Bibliography: p. [290]-306.
School Library Journal.
Young Adult
Keywords: Jogging; Running; Sports -- Psychological aspects; Jogging; Running; Sports -- Psychological aspects